Extensive aquatic subsidies lead to territorial breakdown and high density of an apex predator. Issue 1 (28th November 2021) - Eriksson, Charlotte E.; Kantek, Daniel L. Z.; Miyazaki, Selma S.; Morato, Ronaldo G.; dos Santos‐Filho, Manoel; Ruprecht, Joel S.; Peres, Carlos A.; Levi, Taal
Abstract: Energetic subsidies between terrestrial and aquatic ecosystems can strongly influence food webs and population dynamics. Our objective was to study how aquatic subsidies affected jaguar ( Panthera onca ) diet, sociality, and population density in a seasonally flooded protected area in the Brazilian Pantanal. The diet ( n = 138 scats) was dominated by fish (46%) and aquatic reptiles (55%), representing the first jaguar population known to feed extensively on fish and to minimally consume mammals (11%). These aquatic subsidies supported the highest jaguar population density estimate to date (12.4 jaguars/100 km²) derived from camera traps (8, 065 trap nights) and GPS collars ( n = 13). Contrary to their mostly solitary behavior elsewhere, we documented social interactions previously unobserved between same‐sex adults including cooperative fishing, co‐traveling, and play. Our study demonstrates that aquatic subsidies, frequently described in omnivores, can also transform the ecology and behavior of obligate carnivores.